2009
DOI: 10.1016/j.ejmg.2009.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic genomic imbalances in de novo and inherited apparently balanced chromosomal rearrangements: Array CGH study of 47 unrelated cases

Abstract: Investigations of apparently balanced chromosomal rearrangements in patients with abnormal phenotype by molecular cytogenetics tools, especially by array CGH, revealed a proportion of unsuspected imbalances. It was estimated recently that 40% of apparently balanced de novo translocations with abnormal phenotype were associated with cryptic deletion. We explored 47 unrelated mental retardation patients carrying an apparently balanced chromosomal rearrangement with high-resolution oligonucleotides arrays. We inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 32 publications
5
73
0
8
Order By: Relevance
“…31 However, only ~6% of de novo apparently balanced rearrangements are considered to be pathogenic, 32 and studies have shown that ~40% of apparently balanced rearrangements harbor pathogenic CNVs at the breakpoints, or elsewhere. 33,34 Taken together, it is clear that karyotyping and FISH remain essential tools for accurate prenatal genetic diagnosis, and parental cytogenetic analysis may also be required to achieve a correct diagnosis of recurrence risk as demonstrated by our results and others. Karyotype is required for any family with a known family history of a balanced rearrangement only identifiable by conventional karyotype.…”
Section: Discussionsupporting
confidence: 59%
“…31 However, only ~6% of de novo apparently balanced rearrangements are considered to be pathogenic, 32 and studies have shown that ~40% of apparently balanced rearrangements harbor pathogenic CNVs at the breakpoints, or elsewhere. 33,34 Taken together, it is clear that karyotyping and FISH remain essential tools for accurate prenatal genetic diagnosis, and parental cytogenetic analysis may also be required to achieve a correct diagnosis of recurrence risk as demonstrated by our results and others. Karyotype is required for any family with a known family history of a balanced rearrangement only identifiable by conventional karyotype.…”
Section: Discussionsupporting
confidence: 59%
“…It has been reported that ~40% of patients with multiple congenital anomalies/mental retardation and a de novo apparently balanced translocation have cryptic abnormalities near the breakpoints, or unrelated to the breakpoints, which can be easily detected by CMA. 19,20 However, CMA did not detect any copy number changes near the breakpoints in these 30 cases. Several factors may contribute to this observation.…”
Section: Apparently Balanced Rearrangements With a Normal Cma Studymentioning
confidence: 73%
“…Approximately 40% of reciprocal, cytogenetically balanced de novo translocations associated with abnormal phenotypes have a microdeletion at either one of the breakpoints or elsewhere and should be followed up by chromosome microarray 4 . The prenatal detection of apparently balanced, de novo chromosome rearrangements by conventional cytogenetic techniques should necessarily be followed up with microarray analysis to evaluate the possibility of an imbalance 5 .…”
Section: Discussionmentioning
confidence: 99%
“…DNA segments from across all chromosomes are used as substitutes for metaphase chromosomes, analogous to a molecular karyotype 1 . In addition, approximately 40% of patients with a clinical phenotype and an apparently balanced translocation by conventional cytogenetics have been shown, by chromosome microarray, to carry a cryptic imbalance that would be consistent with their clinical phenotype 4 . In prenatal diagnosis, therefore, chromosome microarray diagnosis is recommended for fetuses with a de novo chromosome rearrangement 5 .…”
mentioning
confidence: 99%